Single-strand conformation polymorphism analysis of variability of the rp0S sequence in environmental and clinical isolates of Salmonella typhi - K.L, Thong,; W. Y, Leong,; Mohamed, Zulqarnain (Malaysian Journal of Science, 2001)
rpoS gene is present in a number of Gram-negative bacteria. lt encodes a sigma factor, which is part of an altemative regulatory system that is known to enhance survival of bacteria in adverse conditions. Mutation screening of the downstream region of rpoS gene in 26 environmental and clinical strains of S. typhi from Santiago, Chile was performed. No polymorphism at the rpoS gene was detected among clinical isolates. On the other hand, environmental isolates had four unique single-stranded conformation polymorphism (SSCP) profiles, in which a dominant profile was shared with the human isolates. The close association of the clinical and environmental isolates in the rpoS gene may suggest a possible epidemiological link between environmental sources and human infection. In addition, SSCP data also indicates possible mutations within the rpoS gene at the downstream region.